Einführung - Leineweber, Jonas (Immaterielles Kulturerbe und Regionale Identität. Schützenwesen in Nordwestdeutschland)

Immaterielles Kulturerbe und Regionale Identität. Schützenwesen in Nordwestdeutschland

Fibering polarizations and Mabuchi rays on symmetric spaces of compact type - Baier, Thomas; Ferreira, Ana Cristina; Hilgert, Joachim; Mourão, José M.; Nunes, João P. (Analysis and Mathematical Physics)

Numerical modeling of clamp load relaxation of plastic nuts under varying moisture and fiber contents - Wippermann, Jan; Meschut, Gerson (Welding in the World)
This study presents a numerical approach using a 3D finite element model to quantify the remaining clamp load of a plastic nut joint after a specific time. The viscoelastic relaxation of a thermoplastic nut, which is predominantly screwed on a welding stud, is described by a material card using Prony Series. Prony Series are derived from experimental dynamical mechanical analysis with different moisture and fiber contents of the thermoplastic. Since plastic nuts usually do not have preformed threads, the increased temperatures and resulting stresses from the thread-forming process are considered in the simulation. An FE model is created and verified by substrate stress relaxation tests. Experimental clamp load measurements with miniature compression load cells verify the clamp load prediction and show a good agreement. The developed model is used to analyze the clamp load distribution within the threads and reveals an almost even distribution within the threads.

Entwicklung einer Methode für die Prognose des Anziehdrehmoments von Kunststoffmutte - Wippermann, Jan; Meschut, Gerson (JOINING PLASTICS)

Ressourceneffiziente Füge- und Entfügetechnologien: Online-Content zum interaktiven Whitepaper KORESIL - Meschut, Gerson; Gilich, Julian; Chudalla, Nick Andre (Komplexität beherrschen, Kreisläufe schließen : Soziotechnische Systeme für ressourceneffiziente Leichtbaustrukturen ; Das interaktive Whitepaper)
Die Transformation der bisher linearen Wirtschaft zu einer Kreislaufwirtschaft und einer möglichst emissionsneutralen Herstellung und Verwendung von Produkten bedarf einer ganzheitlichen Forschung und Entwicklung in allen Bereichen der Prozesskette. Die Fügetechnik gilt dabei als Enabler moderner Hybridstrukturen und ermöglicht die anforderungsgerechte Verbindung artverschiedener Werkstoffe mit unterschiedlichen technisch-wirtschaftlichen Eigenschaftsprofilen. Aktuelle Herausforderungen umfassen das qualitätsgesicherte Fügen bei einer zunehmenden Materialvielfalt aus Primär- und Sekundärwerkstoffen sowie das gezielte Entfügen von Leichtbaustrukturen in Instandsetzungs- oder Recyclingprozessen. Ein weiterer Entwicklungsschwerpunkt liegt auf der menschzentrierten Ausrichtung von Arbeitsprozessen. So können Arbeitskräfte durch eine ergonomische Produktions- und Fügeprozessplanung sowie die Entwicklung und Einbindung prozessbegleitender Mixed-Reality-Technologien gezielt entlastet und dem derzeit zu verzeichnenden Fachkräftemangel effektiv begegnet werden. Das vorliegende Whitepaper zeigt aktuelle Herausforderungen in der Fügetechnik auf, fasst relevante Erkenntnisse und Lösungsansätze aus Industrie und Forschung sowie dem Verbundforschungsvorhaben „Konzepte für die ressourceneffiziente und sichere Produktion von Leichtbaustrukturen“ (KORESIL) zusammen und leitet geeignete Handlungsempfehlungen für die Industrie ab. Diese sollen beteiligten Anwendern strategische Ansätze aufzeigen, um Prozesse ressourceneffizienter und nachhaltiger gestalten zu können.

Effects of various process parameters in the joining process on the squeeze flow of highly viscous thermal interface materials - Gilich, Julian; Teutenberg, Dominik; Meschut, Gerson; Gröger, B.; Wiebicke, F.; Koch, I.; Gude, M. (Welding in the World)
Powertrain concepts incorporating renewable energies are an essential element of the energy revolution and increasingly require efficient manufacturing processes for electronic systems. Particularly, the joining of structures to be thermally coupled, such as the battery modules and the thermal management system (TMS), poses new challenges in process design. Factors that limit the process include the increased density, viscosity, and abrasiveness of thermal pastes as well as the pressure sensitivity of battery modules. The research presented aims to systematically investigate the influences of joining parameters on flow behavior, the formation of air inclusions, and the occurring joining forces to understand and systematically optimize the joining process. Employing a test setup following the Closing-Hele-Shaw-Cell, the influence of specific process parameters on the joining process such as the joining speed, joining gap, application pattern, and temperature was investigated for a silicone- and a polyurethane-based thermally conductive paste. The results indicate a high dependency of both the ensuing joining forces and the flow behavior on the parameters investigated. These insights imply a potential systematic parameter optimization and the specific adaptation of the joining process to improve flow behavior and reduce compressive stresses. This can ensure lower component deformations and qualify the process for the employment of cell types with a higher power density, a reduced encapsulation, and lower stiffness while at the same time improving production rates.

Komplexität beherrschen, Kreisläufe schließen: Soziotechnische Systeme für ressourceneffiziente Leichtbaustrukturen ; Das interaktive Whitepaper
Im Rahmen des BMBF-Forschungsvorhabens KORESIL wurden entlang einer beispielgebenden Prozesskette für hybride Leichtbaustrukturen notwendige Forschungs- und Entwicklungsschwerpunkte ermittelt. Insbesondere die Steigerung der Ressourceneffizienz und die Unterstützung des Menschen im Kontext zukünftiger Arbeitsumfelder standen dabei im Mittelpunkt der Arbeiten. Hierauf aufbauend konnten Handlungsempfehlungen für Wirtschaft, Wissenschaft und Politik abgeleitet werden. Das Projekt KORESIL ist eingebettet in das Projektnetzwerk des Forschungs- und Technologiezentrums für ressourceneffiziente Leichtbaustrukturen – FOREL. Dieses Zentrum wurde im Jahr 2013 als BMBF-Leuchtturmprojekt eingerichtet und ist eine offene, unabhängige Plattform zur Entwicklung von Hightech-Leichtbausystemlösungen in Multi-Material-Design für die Mobilität der Zukunft. Ziel der Plattform ist die Unterstützung von Entwicklungsprojekten, die Vernetzung der Leichtbauforschung innerhalb Deutschlands und die Zusammenführung verschiedener Förderinitiativen.

Investigating the kill cloud: information warfare, autonomous weapons & AI - Bhila, Ishmael (Digital War)
The “kill chain”—involving the analysis of data by human users of military technologies, the understanding of that data, and human decisions—has fast been replaced by the “kill cloud” that necessitates, allows, and exacerbates increased thirst for domination, violence against distant populations, and a culture of experimentation with human lives. This commentary reports an interdisciplinary discussion organised by the Disruption Network Lab that brought together whistleblowers, artists, and experts investigating the impact of artificial intelligence and other emerging technologies on networked warfare. Exposing the problematics of networked warfare and the kill cloud, their colonial overtones, effects on human subjects in real life, erroneous scientific rationalities, and the (business) practices and logics that enable this algorithmic machinery of violence. The conference took place from the 29th of November to the 1st of December 2024 at the Kunstquartier Bethanien in Berlin, Germany.
Keywords: autonomous weapons systems; algorithmic warfare; cloud computing; war on terror

Effects of Early Childhood Teacher Knowledge and Feedback on Children’s Early Mathematical Development in German Kindergartens - Aumann, Lena; Puca, Rosa Maria; Gasteiger, Hedwig (Early Childhood Education Journal)
Abstract Natural everyday situations can offer valuable opportunities for children to develop mathematical ideas. However, as children enter school with widely varying levels of achievement in mathematics, not all children seem to benefit equally from embedded math learning opportunities. To help children take advantage of these opportunities, early childhood (EC) teachers seem to play a significant role in fostering children’s mathematical learning. Previous research suggests that both the teacher’s knowledge and their feedback significantly influence the extent to which children learn. However, most studies on feedback rely on experimental research designs and do not examine naturally occurring feedback in situations involving embedded math learning opportunities. Thus, the influence of EC teachers’ mathematical pedagogical content knowledge (MPCK) and their naturally given feedback on children’s mathematical learning remains underexplored. This paper investigates the effects of naturally given feedback and the MPCK of N = 48 EC teachers on the mathematical development of N = 140 children. Results indicate that process-related feedback positively impacts children’s mathematical development, while other kinds of feedback (e.g., person-related) and teachers’ MPCK do not demonstrate significant effects. These findings highlight the importance of integrating process-related feedback into professional development (PD) programs for EC teachers to enhance their ability to provide effective feedback.

Investigation of local heat treatment strategies for a multi-range capable rivet and the influence on joint formation and load-bearing capacity - Holtkamp, Pia Katharina; Kappe, Fabian; Probst, Paula; Bobbert, Mathias; Meschut, Gerson (Proceedings of the Institution of Mechanical Engineers, Part L: Journal of Materials: Design and Applications)
To reduce CO 2 emissions, the industry, particularly in the mobility sector, focuses on lightweight vehicles with multi-material structures. As thermal joining processes are reaching their limits, mechanical techniques such as self-piercing riveting are being used. One innovative solution is the versatile self-piercing riveting process (V-SPR), which combines different material combinations with a multi-range rivet. 1 The joining process is divided into the piercing process and the forming process of the rivet head to the respective sheet thickness. The rivet shaft requires sufficient strength to punch through the punch-sided sheet, and sufficient ductility of the rivet head is required to form onto the punch-sided sheet. To achieve a combination of these requirements, local inductive heat treatment strategies are used for the rivet. To ensure reproducible rivet hardening, a specialised device has been developed for precise rivet positioning in the induction coil and the subsequent quenching process. The heat treatment differs in terms of hardening times and temperatures. In addition, the heat treatment is combined with a subsequent tempering process. The study aims to determine the resulting hardness distributions and microstructures of the rivet and to investigate the influence of different heat treatment strategies on joint formation and load-bearing capacities. The results show that a graded hardening profile has a positive effect on the spreading behaviour of the rivet foot and the forming behaviour of the rivet head. Furthermore, the load-bearing behaviour of the joints is increased.

Modelling of stress-state-dependent ductile damage with gradient-enhancement exemplified for clinch joining - Friedlein, Johannes; Mergheim, Julia; Steinmann, Paul (Journal of the Mechanics and Physics of Solids)
A coupled finite plasticity ductile damage and failure model is proposed for the finite element simulation of clinch joining, which incorporates stress-state dependency and regularisation by gradient-enhancement of the damage variable. Ductile damage is determined based on a failure indicator governed by a failure surface in stress space. The latter is exemplary chosen as a combination of the Hosford–Coulomb and Cockcroft–Latham–Oh failure criteria for the high and low stress triaxiality range, respectively, to cover the wide stress range encountered in forming. Damage is coupled to elasto-plasticity to capture the damage-induced degradation of the stiffness and flow stress. This affects the material behaviour up to failure, thereby realistically altering the stress state. Consequently, especially for highly ductile materials, where substantial necking and localisation precede material fracture, the failure prediction is enhanced. The resulting stress softening is regularised by gradient-enhancement to obtain mesh-objective results. The analysis of a modified punch test experiment emphasises how the damage-induced softening effect can strongly alter the actual stress state towards failure. Moreover, the impact of successful regularisation is shown, and the applicability of the damage and failure model to clinch joining is proven.
Keywords: Finite plasticity; Ductile damage; Gradient-enhancement; Stress-state dependency; Failure

An applied noise model for scintillation-based CCD detectors in transmission electron microscopy - Zietlow, Christian; Lindner, Jörg K. N. (Scientific Reports)

An applied noise model for low-loss EELS maps - Lindner, Jörg K. N.; Zietlow, Christian (Ultramicroscopy)

The intention-behavior gap in climate change adaptation: Evidence from longitudinal survey data - Osberghaus, Daniel; Botzen, Wouter; Kesternich, Martin (Ecological Economics)
Using a large unique longitudinal survey data set from Germany covering more than 5,000 households, we analyze stated intentions and actual implementations of both flood-proofing and heat stress reduction measures to assess the intention behavior gap (IBG) in climate change adaptation. Our results do not only reveal a substantial IBG for most stated intentions, but also show their limits in serving as a good predictor for realized actions later. Moreover, the IBG itself can hardly be explained by observable household data characteristics. While we do find some similarities in explanatory variables affecting both intentions and implementations, these variables provide only little insights into the actual levels of implemented actions. In line with regret theory, the IBG in our data can be partly explained by anticipated regret caused by a feeling of having invested in vain in cases where adaptation measures are installed, but extreme weather events do not occur for the time being. Our results are informative for adaptation-related communication campaigns and public policy interventions, especially in the aftermath of natural disasters.
Keywords: Intention-behavior gap; Adaptation; Climate Change; Flooding; Heat

Determinanten der politischen Involviertheit von Lehramtsstudierenden und damit verbundene Implikationen für die Lehrer*innenbildung - Wehde, Janis

Thermografische Messungen an Haushaltskältegeräten mit Vakuumisolationspaneele - Potthast, Emily; Elsner, Andreas; Paul, Andreas; Kasper, Tina (Deutsche Kälte- und Klimatagung 2024 Dresden)
In Haushaltskältegeräten werden in den letzten Jahren immer häufiger Vakuumisolationspaneele (VIP) eingesetzt. Hiermit ist es unter anderem möglich, dass die Geräte in die Energieeffizienzklassen A bis C klassifiziert werden können. Ein VIP besteht vereinfacht aus einer Schutzfolie, die nahezu gasdicht ist und einem Füllmaterial, welches für die Formstabilität im Vakuum zuständig ist. Aufgrund von technischen Alterungsprozessen kommt es mit der Zeit zu einem Anstieg des Innendrucks im VIP, wodurch die Wärmeleitfähigkeit des VIP steigt. Je nach Füllmaterial erfolgt dieser Alterungsprozess unterschiedlich schnell. Im Extremfall kann so ein neues Haushalts-kältegerät der Energieeffizienzklasse A nach 1 bis 3 Jahren nur noch als Klasse D bis F eingestuft werden. Innerhalb eines Forschungsprojekts wurden Haushaltskältegeräte mit VIP thermografisch untersucht. Im Rahmen dieser Studienarbeit wurde ein Versuchsaufbau entwickelt, mit dem die zeitliche Veränderung von Wärmebrücken begutachtet werden kann und so Rückschlüsse auf den Effizienzverlust der Geräte möglich sind. Der Funkionsnachweises dieses Versuchsaufbaus wurden an einem Haushaltskältegerät mit künstlich gealterten Vakuumisolationspaneelen durchgeführt. Diese Arbeiten bieten zukünftig die Möglichkeiten Haushaltskältegeräten mit VIP bezüglich ihres Degenerationsverhaltens besser zu beurteilen.
Keywords: Haushaltskältegeräte; Energieaufnahme; Alterung; Isolierung; Vakuumisolationspaneele

Feedback und selbstbezogene Kognitionen als Prädiktoren für die Mathematikleistungen von Grundschulkindern. Vortrag im Rahmen des Symposiums „Lernen durch Feedback von Lehrpersonen, Eltern und Schüler:innen“ (Sebastian Röhl & Fabian Hoya) auf der 12. Tagung der Gesellschaft für Empirische Bildungsforschung (GEBF). Thema: „Bildung als Schlüssel für gesellschaftliche Herausforderungen: Interdisziplinäre Beiträge aus der Bildungsforschung“ - Löper, Marwin Felix; Finke, Nils; Knickenberg, Margarita; Hellmich, Frank

Lead-Free Ceramics in Prestressed Ultrasonic Transducers - Scheidemann, Claus; Bornmann, Peter; Littmann, Walter; Hemsel, Tobias (Actuators)
Today’s ultrasonic transducers find broad application in diverse technology branches and most often cannot be replaced by other actuators. They are typically based on lead-containing piezoelectric ceramics. These should be replaced for environmental and health issues by lead-free alternatives. Multiple material alternatives are already known, but there is a lack of information about their technological readiness level. To fill this gap, a small series of prestressed longitudinally vibrating transducers was set up with a standard PZT material and two lead-free variants within this study. The entire process for building the transducers is documented: characteristics of individual ring ceramics, burn-in results, and free vibration and characteristics under load are shown. The main result is that the investigated lead-free materials are ready to use within ultrasonic bolted Langevin transducers (BLTs) for medium-power applications, when the geometrical setup of the transducer is adopted. Since lead-free ceramics need higher voltages to achieve the same power level, the driving electronics or the mechanical setup must be altered specifically for each material. Lower self-heating of the lead-free materials might be attractive for heat-sensitive processes.

Rechtspopulismus und Rechtsextremismus an Hochschulen - Haker, Christoph (Berliner Debatte Initial)